1979
DOI: 10.1029/gl006i001p00001
|View full text |Cite
|
Sign up to set email alerts
|

Pore fluids and seismic attenuation in rocks

Abstract: Seismic attenuation and velocities were measured in resonating bars of Massilon sandstone at various degrees of saturation. Whereas shear energy loss simply increases with degree of saturation, bulk compressional energy loss increases to ∼95% saturation and then rapidly decreases as total saturation is achieved. This behavior is analogous to the behavior of shear and compressional velocities, but the effect on attenuation is larger by an order of magnitude. Our observations are in excellent agreement with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
158
1
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(182 citation statements)
references
References 22 publications
21
158
1
2
Order By: Relevance
“…The results are shown in Figure 9. It can be seen that P-waves tend to attenuate more than SH-waves, consistent with the theoretical prediction based on the conceptual model of Winkler and Nur (1979) for partially saturated rocks. The opposite behavior observed in the samples (WUK2 at 45°and WUK47B at 90°) can be related in the same way as mentioned above to more intrinsic attenuation caused by the presence of more cracks and fractures in the sample.…”
Section: Samplesupporting
confidence: 76%
“…The results are shown in Figure 9. It can be seen that P-waves tend to attenuate more than SH-waves, consistent with the theoretical prediction based on the conceptual model of Winkler and Nur (1979) for partially saturated rocks. The opposite behavior observed in the samples (WUK2 at 45°and WUK47B at 90°) can be related in the same way as mentioned above to more intrinsic attenuation caused by the presence of more cracks and fractures in the sample.…”
Section: Samplesupporting
confidence: 76%
“…HASEMI et al (1984) attributed the velocity variation to variation in temperature and degree of partial melting. The obtained attenuation structure strongly supports their interpretation because the attenuation reflects the variation of temperature and degree of fluid saturation more sensitively than the velocity does (e.g., JACKSON and ANDERSON, 1970;WINKLER and NUR, 1979). The low-Q zones in layer 2 are intersected by a relatively high-Q zone elongating in the NE-SW direction where volcanoes are distributed sparsely.…”
Section: Attenuation Structuresupporting
confidence: 54%
“…This optimum degree of saturation has been found to increase with a decrease in the grain size of granular material (Cho and Santamarina 2001). It has been noted that the damping ratio decreases continuously with an increase in the confining pressure for sandstone rock (Winkler and Nur 1979). Winkler and Nur (1979) observed that the value of the damping ratio becomes (1) minimum for dry rock, (2) a little higher for partially saturated rock, and (3) maximum for fully saturated rock.…”
mentioning
confidence: 72%